EFEKTIVITAS MEDIA FLASHCARD HURUF BERBASIS TEKNOLOGI DALAM MENINGKATKAN PEMAHAMAN HURUF ABJAD PADA ANAK KELOMPOK B DI TK PERTIWI II KOTA JAMBI - Dini Sanita; Nyimas Muazzomi; Sri Indriani Harianja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Alphabet recognition is a fundamental component of early literacy development in early childhood. However, many children still experience difficulties in identifying letter names, recognizing letter symbols, and associating letters with their initial sounds. These challenges indicate the need for innovative learning media that can enhance children's engagement and understanding during the learning process. This study aimed to examine the effectiveness of technology-based flashcard media in improving alphabet recognition skills among Group B children at TK Pertiwi II Jambi City. The study employed a quantitative approach using a quasi-experimental method with a One-Group Pretest–Posttest Design. The participants consisted of 11 children from Group B (Jeruk Class), who received instruction using technology-based alphabet flashcards over six learning sessions. Data were collected through alphabet recognition tests administered before and after the intervention. The data were analyzed using the Shapiro–Wilk normality test and the Paired Sample t-Test with the assistance of SPSS software. The findings revealed that the mean pre-test score for alphabet recognition was 12.45 (52% of the ideal score), which increased to 21.73 (91%) in the post-test, representing an improvement of 9.27 points. The Paired Sample t-Test yielded a t value of −24.176 with a significance level of 0.000 (p < 0.05), indicating a statistically significant difference between the pre-test and post-test scores. These findings demonstrate that technology-based flashcard media are effective in significantly improving alphabet recognition skills among children aged 5–6 years at TK Pertiwi II Jambi City. Therefore, this learning medium has the potential to serve as an effective instructional tool for supporting early literacy development in early childhood education.